The assessment challenge of social and collaborative learning in higher education - Boud, David; Bearman, Margaret (Educational philosophy and theory, 2024)
There is a general tension between the individualised nature of current assessment practices in higher education and a collaborative approach to learning. This results in many dilemmas for educators as they try to balance academic integrity concerns and student preferences with social or collaborative assessment practices, including peer assessment, group assignments and direct assessment of teamwork or collaboration. This paper argues that focussing on singular assessment tasks or experiences tends to lead to marginal effects. Rather, we suggest that the collaborative must be normalised within course structures: experiences of groupwork, peer learning and other forms of working with others should be commonplace and expected. We look to curricula to provide students with assessable tasks from many rich collaborative experiences, avoid issues of perceived and actual inequity and allow for risk and possible failure. We suggest that grading as presently enacted inhibits collaborative processes and that trust needs to be recognised as central and core to collaborative approaches. The challenges of assessing social and collaborative learning require holistic course wide attention that communicates to both students and colleagues that learning necessarily goes beyond the individual.